L’autorité d’un chef, une véritable magistrature paternelle - Johanne Melcare-Zachara (Cahiers d’histoire)
Considered a being who "lacks physical and intellectual maturity," the child needs special protection and special care. And it is in his family setting, a natural living environment, that he has the best chance of developing harmoniously. Until the end of the 19th century, the family was a private space obeying its internal laws and the State prohibited itself from entering the doors of the house subject to the power of the father, because this was at the very foundation. of social order. Although the Civil Code of 1804 consecrated an absolutism of paternal power, without however going as far as a right of life or death over the child, from the 19th century, a movement in favor of the child developed. which results in a rise in the power of the State and a decline in the power of the father. If the father owes assistance and protection to the child, the fact remains that the latter owes him honor and obedience. And article 371 of the Napoleon Code is there to remind him of this.